Improving Diversity and Promoting Inclusion in the Society for Epidemiologic Research Through Choice of Conference Location - Johnson, Candice Y (Am J Epidemiol, 2020)
Scientific conferences provide attendees opportunities to network, share research, learn new skills and ideas, and initiate collaborations. Conference attendance is especially important for students and early-career researchers who are establishing their research careers or looking for jobs. However, attending conferences can be expensive, and the high cost of conference attendance might hit students and early-career researchers the hardest. According to a new member survey from the Society for Epidemiologic Research, early-career members are more racially and ethnically diverse than senior members, meaning that reducing financial barriers to conference participation might be an important consideration for increasing diversity among conference attendees. In this commentary, we discuss how choice of conference location—choosing less expensive cities nearer to more Society for Epidemiologic Research members—could reduce financial and other barriers to conference attendance for all members and improve diversity and inclusion in the Society.